Kendali LQR berbasis inverse kinematik pada robot lengan 3 derajat kebebasan - Adri Firmansya Sofyan; Erwin Susanto; Rafsanjani Nurul Irsyad; Alfitho Satya Prabaswara; Irham Mulkan Rodiana (LPPM INSTITUT TEKNOLOGI TELKOM PURWOKERTO, 2025)
Linear Quadratic Regulator (LQR) is one of the optimal control methods on state space-based systems. The LQR control method is an option to be applied to the 3 DOF robot arm because multi-link systems such as robot arms are basically non-linear with quite complex modeling. Using conventional control methods has many trade-offs to find optimal stability between the parameters on the robot arm. System modeling is formulated using the Lagrangian dynamics and Euler-Lagrange method to obtain a nonlinear model of the system and then linearized it using Taylor series expansion. The values of the Q and R matrices can be adjusted to obtain a good system response for a particular trajectory. Tunning the Q and R parameters can also improve the stability of the system by reducing overshoot but causing the rise time of the system to increase